Genetic characteristics and potential pathogenic agents in Campylobacter upsaliensis based on genomic analysis - Hairui Wang; Yixin Gu; Changyan Ju; Ying Li; Xiaoli Chen; Guilan Zhou; Xin Zhang; Chang Liu; Jing Chen; Yue Han; Jianzhong Zhang; Zhujun Shao; et al. (Emerging Microbes and Infections)
Campylobacter upsaliensis was the most common Campylobacter species in pets’ gastrointestinal tracts and has been isolated from patients with bacteremia, hemolytic-uremic syndrome, spontaneous abortion, and Guillain-Barré syndrome. However, the genetic characteristics and the full extent of its significance as a human pathogen remain to be fully understood. This study involved an investigation for genomic analysis of 154 strains from different sources and additional antimicrobial resistance profiles of 26 strains for this species. The genomes contained 1,558–1,971 CDS and the genome sizes were estimated to vary from 1.53 Mb to 1.86 Mb, with an average GC content of  34.71%. The entire analyzed genomes could be divided into three clades (A, B, and C) based on ANI and phylogenomic analysis. Significantly, nearly all strains in Clade B were isolated from patient samples, and the virulence-related sequences FlgD, GmhA, and CdtC might serve as determining factors for the classification of Clade B. Half of the tested isolates had MIC values over 64 μg mL−1 for nalidixic acid, gentamicin, and streptomycin. Isolates from pets in China carried more resistant elements in the genomes. This study both provided a comprehensive profile of C. upsaliensis for its genomic features and suggested some pathogenic agents for human infection with this species.